Reconstruction of cultural views of 'reluctant' prevents criminal acts of gratification - Galih Puji Mulyono; Yusuf Eko Nahuddin; Lily Faradina; Sri Indah Cahyani (Jurnal Cakrawala Hukum, 2022)
This study aims to reconstruct the "reluctant" cultural view and minimize the level of gratification in the ULP employees of the Batu City Government. The method used is empirical research, with the research location being the Batu City Government Procurement Service Unit. The results of this study are activities carried out by making slogans for Batu City Government ULP employees who read the anti-Gratification slogan and categorize the culture of shame as positive and negative. Next, is the design of a blueprint for the Batu City Government ULP code of ethics, carried out through a Focus Group Discussion. The discussion in this study shows that 90% of ULP officials in the Batu City Government still do not understand gratification and do not yet have a draft code of ethics that regulates ULP in the Batu City Government, primarily through the education provided by the leadership. Therefore, it is essential that this research and should be carried out by implementing the above results can reduce the crime of gratification in Indonesia.How to cite item:Â Mulyono, G., Nahuddin, Y., Faradina, L., Cahyani, S. (2022). Reconstruction of cultural views of 'reluctant' prevents criminal acts of gratification.Â Jurnal Cakrawala Hukum, 13(2), 155-163. DOI:https://doi.org/10.26905/idjch.v13i2.7965.